Photoresponse properties of poly(3-hexylthiophene) (P3HT) based photodiode - Ilter, Zulfiye (Elsevier Science Bv, 2019)
A photosensor based poly(3-hexylthiophene) (P3HT) and phenyl-C61-butyric acid methyl ester (PCBM):graphene oxide (GO) (P3HT:PCBM:GO) was prepared by spin coating method. Poly(3-hexylthiophene) based composite was prepared by FYTRONIX nanomaterial production system. The photoresponse characteristics of the poly(3-hexylthiophene) (P3HT):phenyl-C61-butyric acid methyl ester (PCBM):graphene oxide (GO), (P3HT:PCBM:GO) based photodiode was measured under various solar illuminations. The photocurrent-voltage-time characteristics of P3HT:PCBM:GO/p-Si diode exhibits a photodiode behavior with photocurrent parameters. The rise and drop time values of the diode were obtained under various illuminations. The ratio of photocurrent to dark current was obtained to be 1.38 x 10(3) under 100 mW/cm(2). The interface behavior of the diode was analyzed by capacitance-voltage characteristics. The charge separation of the diode is changed with light illuminations. The optoelectronic characteristics of P3HT:PCBM:GO diode suggest that the studied is a promising photosensor for optoelectronic system applications.
Keywords: Photodiode; P3HT:PCBM:GO and photoresponse